2020
DOI: 10.1126/scitranslmed.aba0599
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocyte-derived extracellular vesicles as antigen-specific therapy for autoimmune neuroinflammation in mice

Abstract: Autoimmune diseases such as multiple sclerosis (MS) develop because of failed peripheral immune tolerance for a specific self-antigen (Ag). Numerous approaches for Ag-specific suppression of autoimmune neuroinflammation have been proven effective in experimental autoimmune encephalomyelitis (EAE), an animal model of MS. One such approach is intravenous tolerance induction by injecting a myelin Ag used for triggering EAE. However, the translation of this and similar experimental strategies into therapy for MS h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 51 publications
(99 reference statements)
0
48
0
Order By: Relevance
“…While it is not possible to fully dissect the functional impact of free or EV-encapsulated mitochondria separately, our data strongly suggest that mitochondria in EV preparations, and the CD63 + EV fraction, are indispensable for the in vivo therapeutic effect. In addition to classical cellular grafts [37], these new data further support the use of EV-based acellular therapies in regenerative neuroimmunology [70].…”
Section: Discussionmentioning
confidence: 78%
“…While it is not possible to fully dissect the functional impact of free or EV-encapsulated mitochondria separately, our data strongly suggest that mitochondria in EV preparations, and the CD63 + EV fraction, are indispensable for the in vivo therapeutic effect. In addition to classical cellular grafts [37], these new data further support the use of EV-based acellular therapies in regenerative neuroimmunology [70].…”
Section: Discussionmentioning
confidence: 78%
“…This EV-based vaccine was safe and restored immune tolerance by inducing immunosuppressive monocytes and apoptosis of autoreactive CD4+ T cells. These findings introduce an approach to suppressing CNS autoimmunity in a myelin antigen-specific manner, without the need to identify the target antigens [88].…”
Section: Role Of Extracellular Vesicles As Preventative Treatment For Multiple Sclerosismentioning
confidence: 97%
“…However, the relevant self-myelin antigen in MS remains speculative, with the possibility that these antigens differ among patients and over time in the same patient. It has been shown that PLP is mainly present in small EVs, which are enriched in exosomes, whereas MBP and MOG are mainly present in large EVs, specifically the fraction enriched in microvesicles [88]. Given that EVs include exosomes and microvesicles, Casella et al used total EVs from oligodendrocytes (which naturally contain most of the relevant myelin antigens) as an EV-based vaccine in various experimental animal models of MS.…”
Section: Role Of Extracellular Vesicles As Preventative Treatment For Multiple Sclerosismentioning
confidence: 99%
“…Recently the same group have shown that, naturally derived EVs from oligodendrocytes culture contains myelin antigens and transfer of this EVs reduce EAE pathophysiology in a myelin antigen-dependent manner in EAE models [77]. Interestingly EVs derived from MSC protects oligodendrocytes from DNA damage and EVs from MSC co-cultured with microglia helps the myelin repair by recruiting oligodendrocyte precursor (OPC) in demyelinated regions [78,79].…”
Section: Evs In Ms Therapymentioning
confidence: 99%